Manajemen Kurikulum Berbasis Pendidikan Islam Masa Pandemi Covid-19 - Devi Vionitta Wibowo; Erni Munastiwi; Ahmad Sanusi (JURNAL PENELITIAN KEISLAMAN, 2021)
The purpose of this article is to determine the management of an Islamic education-based emergency curriculum at RA Masyithoh to make effectively and efficiently for Islamic education during pandemic-19. The research method used qualitative methods with investigations and interviews. The results of the study indicate that there is an implementation of an Islamic education-based emergency curriculum management which includes planning, organizing, implementing, and evaluating in order to create an Islamic education with character in accordance with the guidance of the Al-Qur'an and the Prophet's Hadith. The institution makes SOP related to additional work programs in the form of study guidance, parenting, media collection and screening of children's learning outcomes which is carried out once a week. There is an increase in teacher performance and an increase in independence and discipline in children character when implementing Islamic education-based emergency curriculum at RA Masyithoh Rembang.